The Effect of Emotion Regulation-Based Group Therapy on Alexithymia and Experiential Avoidance in Substance Use Patients, with Borderline Personality Disorder - Shirin Dehban; changhiz rahimi (مطالعات روانشناختی, 2021)
The purpose of this study was to evaluate the effectiveness of group therapy based on emotion regulation on alexithymia, and experiential avoidance in substance user patient with comorbidity of borderline personality disorder. The research design was quasi-experimental with two experimental and control groups including pre-test and post-test. The statistical population of this study consisted of patients with substance abuse disorder and borderline personality in a psychiatric hospital of Shiraz city; 30 persons (male) were selected using purposive sampling method and randomly assigned in the study: One experimental and one control group (15 males each). The criteria for entry into treatment were borderline personality disorder diagnosis with substance abuse and methadone maintenance treatment. The tools used in this study were Toronto-20 mood disorder questionnaire and Second Edition Acceptance and Practice Questionnaire to assess experiential avoidance. Data were analyzed using covariance analysis and descriptive statistics. The results showed that the scores of alexithymia, and experiential avoidance significantly decreased in the experimental group after the treatment. The results of this study illustrated that group therapy based on emotion regulation can reduce alexithymia, and experiential avoidance in this group of people. Therefore, it is suggested that in addition to pharmacological treatments, psychological treatment methods may also be used to increase the effectiveness of treatment on drug users.